Analisis Pola Ucap Humoris dalam Majalah Manglé Rubrik “Barakatak” (Kajian Pragmatik) - Setiawan, Budi Rahayu; Hemalia, Alisha; Permana, Vira Vandini; Rahmatilah, Lola Apriani; Putry, Keisya Aurelya; Widyastuti, Temmy; Hernawan, Hernawan (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
This study aims to explore the use of humorous speech acts in the Barakatak column of Manglé magazine as a reflection of pragmatic communication within the Sundanese cultural context. Humor in local, regionally-based media plays a vital role in conveying social criticism and preserving the existence of indigenous languages. However, linguistic research on local humor—especially from a pragmatic perspective—remains notably limited. This research employs a qualitative descriptive method with a pragmatic approach. The data consist of humorous texts extracted from the Barakatak column in the September–October editions. Various types of speech acts were identified, including locutionary, illocutionary, and perlocutionary acts. Furthermore, each entry was found to contain humor functions such as commissive, impositive, expressive, and assertive functions. Lastly, numerous forms of sociocultural criticism were discovered, illustrating the embodiment of local wisdom in Sundanese culture. The analysis of eleven Barakatak entries revealed key patterns in speech acts, humor functions, and cultural context. These findings indicate that the humor presented in Barakatak serves not merely as entertainment, but also as an effective and nuanced form of cultural communication for articulating social criticism within the Sundanese community.